Analysis of Sea Water Pollution Status Using Gastropoda as Bioindicators in The Amahami Mangrove Area of Bima City - Zakaria Zakaria; Rahmayang Trintyani (Journal of Biology, Environment, and Edu-Tourism, 2025)
The Amahami mangrove area in Bima City is damaged, where mangrove trees are cut down for the construction of markets, parks and cut down by the surrounding community for the needs of ships and houses, not only that, the entire Amahami mangrove area has been polluted by piles of garbage. This study is about the Analysis of Water Pollution Status Using Gastropods as Bioindicators in the Amahami Mangrove Area of ​​Bima City with the aim of determining the status of water pollution using gastropods as bioindicators in the Amahami Mangrove Area of ​​Bima City. This study uses a descriptive research type using line transects. Descriptive research is conducted to describe or explain systematically, factually and accurately about the facts and characteristics of the population. The study was conducted in January 2025 with a design in 3 transects, each of which has 4 plots measuring 2x2 m, the transects are stretched along the mangrove area and the sampling method is proposive sampling. Data analysis includes the Shannon-Wienner diversity index and Analysis of physical and chemical parameters. The results of this study show that the status of water pollution in the Amahami Mangrove Area of ​​Bima City shows that at location I, namely in the area after the Amahami Park, Bima City, the H' Index value is 1.3 < 1.5 or is in the polluted category, location II, namely the central area of ​​the Amahami mangrove area, Bima City with an H' index value of 1.7 < 2.0 or lightly polluted and at location III, namely the mangrove area close to Lawata Beach, Bima City, there is an H' index value of 0.9 < 1.0 or heavily polluted.